2009
DOI: 10.3727/109830510x12670455864203
|View full text |Cite
|
Sign up to set email alerts
|

Improving Recommendation Effectiveness: Adapting a Dialogue Strategy in Online Travel Planning

Abstract: Conversational recommender systems support a structured human-computer interaction in order to assist online tourists in important online activities such as travel planning. In this article we describe the effects and advantages of a novel recommendation methodology based on Machine Learning techniques that allows conversational systems to autonomously improve an initial strategy in order to learn a new one that is more effective and efficient. We applied and tested our approach within a prototype of an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 16 publications
(4 reference statements)
0
17
0
Order By: Relevance
“…An MDP model, deployed to an online bookstore, was found to generate recommendations which outperformed commercially available collaborative filtering methods in successfully recommending items to users [Shani et al 2005]. In another study, it was found that users of a vacation planning website were more inclined to follow recommendations generated by an MDP than a linear policy, resulting in a more efficient search session for the user [Mahmood et al 2009]. MDP methods are, however, not without drawbacks.…”
Section: Markov Decision Processesmentioning
confidence: 99%
“…An MDP model, deployed to an online bookstore, was found to generate recommendations which outperformed commercially available collaborative filtering methods in successfully recommending items to users [Shani et al 2005]. In another study, it was found that users of a vacation planning website were more inclined to follow recommendations generated by an MDP than a linear policy, resulting in a more efficient search session for the user [Mahmood et al 2009]. MDP methods are, however, not without drawbacks.…”
Section: Markov Decision Processesmentioning
confidence: 99%
“…In the travel and tourism domain, such systems are for example developed to help the customer in the pre-trip information search and decision making process. Examples of recent research include knowledge-based and conversational approaches to filter destinations and select travel packages (Jannach et al 2009(Jannach et al , 2007Zanker et al 2008), context-aware recommendation of places of interest (Baltrunas et al 2011), mobile recommenders (Ricci 2011), or the development of more intelligent user interaction strategies (Mahmood et al 2009). …”
Section: Relation To Other Workmentioning
confidence: 99%
“…For instance, by exploiting a set of features for each tourist's specific interaction session, Ricci et al described two case-based reasoning approaches Ricci et al [2006aRicci et al [ , 2006b for travel recommendation and advisory. Mahmood et al [2009] used conversational systems to autonomously improve the recommendation strategy and applied their approach within a prototype of an online travel recommender system. Mahmood et al [2009] used conversational systems to autonomously improve the recommendation strategy and applied their approach within a prototype of an online travel recommender system.…”
Section: Related Workmentioning
confidence: 99%